Analysis of Child Marriage Issue in Indonesia from the Qirā'ah Mubādalah Perspective - Abdul Muqsid; Faricha Cahya Fajrianti; Nabila Amalia (JOSAR (Journal of Students Academic Research), 2026)
This study aims to critically examine the practice of child marriage, which is often legitimized through a literal reading of Islamic texts, particularly the Qur’an and Hadith. Such textual interpretations frequently disregard the Islamic ethical framework that emphasizes justice, dignity, and the protection of children. This study is qualitative in nature, employing library research and utilizing a textual-contextual analysis method. It adopts the mubādalah perspective, a hermeneutic framework that emphasizes reciprocity, equality, and mutual responsibility. This article reinterprets hadiths regarding marriage, specifically the terms syabāb (youth) and al-ba’ah (capacity). The analysis reveals that these terms require readiness, consent, and equal capacity between men and women as dignified subjects. In the context of child marriage, this readiness is clearly not met, as girls face biological, psychological, and social limitations that pose risks of maternal and infant mortality, school dropout, and a cycle of poverty. The research findings affirm that child marriage contradicts the principles of martabah (dignity), ‘adālah (justice), and maṣlaḥah (public interest). The contribution of this study is to offer a reinterpretation of hadith based on humanistic Islam that rejects child marriage, as well as to reaffirm Islam as a source of protection, equality, and respect for human dignity